PENATALAKSANAAN HOLISTIK PADA PRIA USIA DEWASA MUDA DENGAN GANGGUAN CEMAS MENYELURUH DAN KEPRIBADIAN INTROVER MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Mhd. Nur Ridha Asshaf; Diana Mayasari (Medula, 2023)
Anxiety disorders are a group of conditions that have characteristics in the form of excessive anxiety conditions, accompanied by behavioral, physiological, and emotional changes of the person. Behaviors found in individuals with anxiety disorders include panic for no reason, excessive and unwarranted fear of objects or living conditions, and unexplained worry. By identifying risk factors, clinical problems, and providing management to patients with the application of holistic family doctor services based on evidence-based medicine. This study is a case report. Primary data are obtained through history and physical examination. Secondary data is obtained from the patient's medical record at the Puskesmas. Assessment is carried out based on a holistic diagnosis of the beginning, process, and end of the study quantitatively and qualitatively. Assessment based on the initial holistic diagnostics, process and end of study qualitatively and quantitatively. Mr. A, 35, came in for routine control of his excessive anxiety. The results of the axial diagnosis are established Axis 1 of generalized anxiety disorder (F41.1). Axis 2 there is no diagnosis. Axis 3 there is no diagnosis.  Axis 4 patients have problems related to the social environment. Axis 5 patient GAF score 70-61.  When measured using the Penn State Worry Questionnaire, a score of 45 was obtained. Patients are intervened holistically using a family doctor approach. The patient's final diagnostic results have applied an intervention in the form of Cognitive Behavior Therapy and when remeasured using the Penn State Worry Questionnaire obtained a value of 29 which means not in a state of anxiety that interferes